The Density Value of Mixing Water and Cooking Oil Using an Emulsifier (Tween 20) (DINAMIS, 2024)
Water and cooking oil are fluids that we often encounter in our daily lives and are often needed. Water is polar while cooking oil is non-polar, so in uniting the two fluids an emulsifier (Tween 20) is used to mix them. The aim of this research is to combine polar and non-polar fluids. Emulsifier (Tween 20) is used as a polysorbate surfactant (mixing agent) for the two fluids and can mix perfectly. The combined water and oil are mixed using a mixing stirrer with a speed of 100-200 rpm, a temperature of 70â°C, within 1 hour. To obtain a fluid density value by providing heating from 30â°C-90â°C, then inserting it into a 25 ml volumetric flask and weighing it. After mixing, a white hybrid fluid will be produced, and it will separate again when the fluid is at room temperature.